Japan's nationalist right in the Internet age: : online media and grassroots conservative activism - Hall, Jeffrey J. (Jeffrey James) (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"Japan's nationalist right have used the internet to organize offline activism in increasingly visible ways. Hall investigates the role of internet-mediated activism in Japan's ongoing historical and territorial disputes. He explores the emergence of two right-wing activist organizations, Nihon Bunka Channel Sakura and Ganbare Nippon, which have played a significant role in pressure campaigns against Japanese media outlets, campaigns to influence historical memorials, and campaigns to assert Japan's territorial claim to the Senkaku/Diaoyu Islands. Taking a multi-disciplinary approach, he analyses how activists maintained cohesion, raised funds, held protests that regularly drew hundreds to thousands of participants, and used fishing boats to land activists on disputed islands. Detailing events that took place between 2004 and 2020, he demonstrates how skilled social actors built cohesive grassroots protest organizations through the creation of shared meaning for their organization and its supporters. A valuable read both for scholars seeking insight into the dynamics surrounding Japan's history disputes and territorial issues, as well as those seeking to compare Japanese right-wing internet activism with its counterparts elsewhere"--
OCLC-licensed vendor bibliographic record.
Keywords: Right-wing extremists -- Japan; Nationalism -- Japan; Internet and activism -- Japan; Internet -- Political aspects -- Japan